(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Physical and physiological frailty associated with human ageing has a significant impact on the immune system. In this setting, ageing is linked to innate and adaptive immune reductions known as immunosenescence. The term "immunosenescence" describes the reorganisation of innate and adaptive immune functions that occurs with ageing. Therefore, chronic low-level inflammation, greater infection rates, and chronic illnesses are typically found in aged people. A biomarker for assessing immunological senescence therapy may be discovered through research on immune system changes that occur with ageing. The interaction of innate and adaptive immunity leads to the immune system, although it is unknown how ageing affects this process. This article investigates how the immune system works as we age.